Use of ultrasound to monitor biceps femoris mechanical adaptations after injury in a professional soccer player - Kellis, E.; Galanis, N.; Chrysanthou, C.; Kofotolis, N. (Journal of Sports Science & Medicine, 2016)
This study examined the use of ultrasound to monitor changes in the long head of the biceps femoris (BF) architecture of aprofessional soccer player with acute first-time hamstring strain. The player followed a 14 session physiotherapy treatment until return to sport. The pennation angle and aponeurosis strain of the long head of the biceps femoris (BF) were monitored at 6 occasions (up until 1 year) after injury. The size of the scar / hematoma was reduced by 63.56% (length) and 67.9% (width) after the intervention and it was almost non-traceable one year after injury. The pennation angle of the fascicles underneath the scar showed a decline of 51.4% at the end of the intervention while an increase of 109.2% of the fascicles which were closer to deep aponeurosis was observed. In contrast, pennation angle of fascicles located away from the injury site were relatively unaffected. The treatment intervention resulted in a 57.9% to 77.3% decline of maximum strain per unit of MVC moment and remained similar one year after the intervention. This study provided an example of the potential use of ultrasound-based parameters to link the mechanical adaptations of the injured muscle to specific therapeutic intervention